A multi-modal corpus approach to the analysis of backchanneling behaviour - Knight, Dawn (2009)
Current methodologies in corpus linguistics have revolutionised the way we look at language. They allow us to make objective observations about written and spoken language in use. However, most corpora are limited in scope because they are unable to capture language and communication beyond the word. This is problematic given that interaction is in fact multi-modal, as meaning is constructed through the interplay of text, gesture and prosody; a combination of verbal and non-verbal characteristics.